2017
DOI: 10.2139/ssrn.3065282
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-Mechanical Aspects of the L. Pauling's Resonance Theory.

Abstract: The L. Pauling's resonance theory analyzed using principle of quantum superposition, that is the principle of superposition "wave function", which is the main positive principle of quantum mechanics. The principle of quantum superposition is essentially a basic property of the wave function. By example of benzene molecule is shown that the principle of quantum superposition, and hence the quantum mechanics in general is in insurmountable conflict with the resonance theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…It is also especially worth noting that when analyzing the Pauli principle 4. It is shown [11,17] that the main assumption of the molecular orbitals method (namely, that the molecular orbital can be represented like a linear combination of overlapping atomic orbitals) enters into an insurmountable contradiction with the principle of quantum superposition. It is also shown that the description of a quantum system consisting of several parts (adopted in quantum mechanics) actually prohibits ascribe in VB method to members of equation corresponding canonical structures.…”
Section: Notes On the Chemical Bondmentioning
confidence: 99%
“…It is also especially worth noting that when analyzing the Pauli principle 4. It is shown [11,17] that the main assumption of the molecular orbitals method (namely, that the molecular orbital can be represented like a linear combination of overlapping atomic orbitals) enters into an insurmountable contradiction with the principle of quantum superposition. It is also shown that the description of a quantum system consisting of several parts (adopted in quantum mechanics) actually prohibits ascribe in VB method to members of equation corresponding canonical structures.…”
Section: Notes On the Chemical Bondmentioning
confidence: 99%